ACTUAL PROBLEMS OF RAW MATERIALS CHEMICAL STANDARDIZATION OF MEDICINAL PLANTS OF THE GENUS HAWTHORN ΈCRATAEGUS L.Ή - T. V. Morozova; V. A. Kurkin; O. E. Pravdivtseva (Фармация и фармакология (Пятигорск))
The plants of the genus Hawthorn (Crataegus L.) are shrubs or small trees that have been used in medicine since ancient times. Nowadays, on the basis of raw hawthorn, the preparations are available for treatment and prevention of heart failure. The aim of the work is to analyze and systematize research results in the fi eld of chemical standardization of hawthorn raw materials in pharmacopoeias of various countries. Materials and methods. The study was conducted with the use of the State Pharmacopoeia of the USSR, XI-th edition, the State Pharmacopoeia of the Russian Federation, XIII-th edition, the European Pharmacopoeia, 6-th edition, the United States Pharmacopeia, 32-nd editions, the State Pharmacopoeia of the Republic of Belarus and the Republic of Kazakhstan, as well as the information and search (PubMed) and library databases (eLibrary). Results and discussion. In this review, the results of research in the fi eld of chemical standardization of hawthorn raw materials in pharmacopoeias of various countries are systematized. It is determined that in the methods of analysis of raw materials of the species of the genus Hawthorn (Crataegus L.), included in domestic and foreign Pharmacopoeias, various methodological and methodological approaches to the standardization of fruits, fl owers and leaves are used. Besides, it has been found out that the raw materials of the same name are analyzed using different techniques. In our opinion, the use of various extractants in the methods is not always justifi ed from the point of view of the physical-chemical and spectral characteristics of the substances being analyzed. It is also shown that in the methods of qualitative and quantitative analysis of active substances (fl avonoids, procyanidins), the orientation to diagnostically signifi cant standard substances is not always conducted. Conclusion. The analysis of existing methods of qualitative analysis (the section of authenticity) and quantitative determination of the target substances indicates the necessity to unify the methods of raw materials analysis and preparations of hawthorn species on the basis of scientifi cally based approaches to standardization.